2001
DOI: 10.1364/ol.26.000701
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of optode arrangements for diffuse optical tomography: A singular-value analysis

Abstract: We develope a method to optimize the resolution of diffuse optical tomographic instruments. Singular-value analysis of the tomographic weight matrix associated with specific data types, geometries, and optode arrangements is shown to provide a measure of image resolution. We achieve optimization of device configuration by monitoring the resolution measure described. We introduce this idea and demonstrate its utility by optimizing the spatial sampling interval and field-of-view parameters in the parallel-plane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(124 citation statements)
references
References 14 publications
2
122
0
Order By: Relevance
“…It requires, however, that an instrument allows to measure at several different source detector distances with overlapping light paths and inherently means that the instrument needs a high dynamic range (Boas et al, 2004). Culver et al (2001) simulated the influence of the density of sources and detectors on the image resolution. They found that resolution depends on the SNR of the measurement, the depths of the object and density of sources and detectors.…”
Section: Probe Designmentioning
confidence: 99%
“…It requires, however, that an instrument allows to measure at several different source detector distances with overlapping light paths and inherently means that the instrument needs a high dynamic range (Boas et al, 2004). Culver et al (2001) simulated the influence of the density of sources and detectors on the image resolution. They found that resolution depends on the SNR of the measurement, the depths of the object and density of sources and detectors.…”
Section: Probe Designmentioning
confidence: 99%
“…As diffuse optical imaging measurements on the adult human head typically have sourcedetector separations of 2-4 cm, the head can be considered a semiinfinite medium locally. This simplistic assumption enables an analytic solution of the diffusion equation (Bonner et al, 1987;Haskell et al, 1994;Kienle and Patterson, 1997b) to be used for simulations to test the accuracy and resolution of diffuse optical imaging experiments (Culver et al, 2001;Koizumi et al, 2003). Such simplified simulations are valuable for guiding the optimization of experimental design, which can then be verified with more sophisticated simulations.…”
Section: Diffuse Optical Imaging Forward and Inverse Problem Basicsmentioning
confidence: 99%
“…[9], 900 data points in Ref. [10]). This can be explained by the high computational complexity of algebraic image reconstruction algorithms which scales as O(N 3 ).…”
Section: Introductionmentioning
confidence: 99%